An evaluation of surface meteorology and fluxes over the Iceland and Greenland Seas in ERA5 reanalysis: The impact of sea ice distribution. (20th November 2020) - Renfrew, I. A.; Barrell, C.; Elvidge, A. D.; Brooke, J. K.; Duscha, C.; King, J. C.; Kristiansen, J.; Cope, T. Lachlan; Moore, G. W. K.; Pickart, R. S.; Reuder, J.; Sandu, I.; et al.
Abstract: The Iceland and Greenland Seas are a crucial region for the climate system, being the headwaters of the lower limb of the Atlantic Meridional Overturning Circulation. Investigating the atmosphere–ocean–ice processes in this region often necessitates the use of meteorological reanalyses—a representation of the atmospheric state based on the assimilation of observations into a numerical weather prediction system. Knowing the quality of reanalysis products is vital for their proper use. Here we evaluate the surface‐layer meteorology and surface turbulent fluxes in winter and spring for the latest reanalysis from the European Centre for Medium‐Range Weather Forecasts, i.e., ERA5. In situ observations from a meteorological buoy, a research vessel, and a research aircraft during the Iceland–Greenland Seas Project provide unparalleled coverage of this climatically important region. The observations are independent of ERA5. They allow a comprehensive evaluation of the surface meteorology and fluxes of these subpolar seas and, for the first time, a specific focus on the marginal ice zone. Over the ice‐free ocean, ERA5 generally compares well to the observations of surface‐layer meteorology and turbulent fluxes. However, over the marginal ice zone, the correspondence is noticeably less accurate: for example, the root‐mean‐square errors are significantly higher for surface temperature, wind speed, and surface sensible heat flux. The primary reason for the difference in reanalysis quality is an overly smooth sea‐ice distribution in the surface boundary conditions used in ERA5. Particularly over the marginal ice zone, unrepresented variability and uncertainties in how to parameterize surface exchange compromise the quality of the reanalyses. A parallel evaluation of higher‐resolution forecast fields from the Met Office's Unified Model corroborates these findings. Abstract : Spatial maps of sea‐ice distribution from 8 March 2018 with sensible heat flux (W·m −2 ) overplotted as dots. The top panel shows satellite‐derived sea‐ice fraction contours from AMSR2 with aircraft observations. The bottom panel shows sea‐ice fraction contours from OSTIA with ERA5 output. Note that the OSTIA sea‐ice distribution is used in ERA5 and is, incorrectly, too smooth across the marginal ice zone, which has an impact on the accuracy of surface‐layer meteorology and turbulent fluxes.